2020
DOI: 10.1101/2020.12.03.410621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Affinity Interactions to Prolong Drug Delivery of Protein Therapeutics

Abstract: While peptide and protein therapeutics have made tremendous advances in clinical treatments over the past few decades, they have been largely hindered by their ability to be effectively delivered to patients. While bolus parenteral injections have become standard clinical practice, they are insufficient to treat diseases that require sustained, local release of therapeutics. Cyclodextrin-based polymers (pCD) have been utilized as a platform to extend the local delivery of small-molecule hydrophobic drugs by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In guest-host delivery systems, the diffusive release of guest drug molecules is prolonged by complex dissociation and subsequent re-association events that can sustain release for a period of weeks to months. [82][83][84][85] We first sought to establish that celastrol is a suitable molecular guest for complexation with CD, necessary for inclusion within the CDNP drug carrier. The equilibrium binding constant (K eq ) was determined to be 0.474 mM by equilibrium analysis using surface plasmon resonance (Fig.…”
Section: Papermentioning
confidence: 99%
“…In guest-host delivery systems, the diffusive release of guest drug molecules is prolonged by complex dissociation and subsequent re-association events that can sustain release for a period of weeks to months. [82][83][84][85] We first sought to establish that celastrol is a suitable molecular guest for complexation with CD, necessary for inclusion within the CDNP drug carrier. The equilibrium binding constant (K eq ) was determined to be 0.474 mM by equilibrium analysis using surface plasmon resonance (Fig.…”
Section: Papermentioning
confidence: 99%
“…2 Our laboratory has previously explored insoluble, polymerized cyclodextrin (pCD) for small hydrophobic drug refilling, and demonstrated its use for many applications including treating cancer, infections, and inflammation. 2,[15][16][17][18][19][20] Previous work from our lab has also shown that polymers lacking a particular affinity structure (e.g. polymethylmethacrylate (PMMA)) lack drug refilling capabilities.…”
Section: Introductionmentioning
confidence: 99%